2000
DOI: 10.1161/01.cir.101.17.2026
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive, Transthoracic, Low-Frequency Ultrasound Augments Thrombolysis in a Canine Model of Acute Myocardial Infarction

Abstract: In vivo, the noninvasive transthoracic application of low-frequency ultrasound (1) greatly augments the efficacy of t-PA-mediated thrombolysis, (2) seems safe, and (3) has substantial potential as a noninvasive adjunct to improve coronary patency without increasing the risk of bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
2
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 18 publications
0
61
2
5
Order By: Relevance
“…In a canine coronary artery thrombus model, transcutaneous 27-kHz US along with rt-PA demonstrated significant recanalization (Siegel et al 2000). Microbubble potentiation of thrombolysis in intracranial arteries was demonstrated in a porcine model by Culp et al (2003) using 1-MHz US.…”
Section: Discussionmentioning
confidence: 89%
“…In a canine coronary artery thrombus model, transcutaneous 27-kHz US along with rt-PA demonstrated significant recanalization (Siegel et al 2000). Microbubble potentiation of thrombolysis in intracranial arteries was demonstrated in a porcine model by Culp et al (2003) using 1-MHz US.…”
Section: Discussionmentioning
confidence: 89%
“…In a canine model, they demonstrated that application of transcutaneous ultrasound near the site of an occluded femoral artery, when used in conjunction with tPA infusion, resulted in an 80% decrease in time for recanalization [30]. Similarly, in canine models of acute coronary occlusions, transcutaneous ultrasound augmented the efficacy of tPA-facilitated thrombolysis, regardless of whether the anterior or posterior coronary circulations were involved [31,32]. For the clinical application of noninvasive ultrasound therapy, it may be advantageous to determine the exact location of the clot in order to selectively insonify the area of interest, thus limiting potential harmful bioeffects to surrounding tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Stable cavitation is characterized by bubbles pulsating gently in response to the time-varying acoustic pressure in an ultrasound field. Siegel et al found that noninvasive transthoracic application of low-frequency (27 kHz) ultrasound augmented the efficacy of t-PA-mediated thrombolysis in a canine model, and improved coronary patency without increasing the risk of bleeding [23].…”
Section: Introductionmentioning
confidence: 99%